2018
DOI: 10.1007/s10120-018-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 30-day hospital readmission after radical gastrectomy: a single-center retrospective study

Abstract: CRP on POD3 ≥ 12 mg/dl, laparoscopic surgery, and TG were identified as independent risk factors for readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…As demonstrated in Tables 1 and 2 , the length of hospital stay in IAI patients was significantly longer in terms of short-term prognosis. Studies have revealed that intra-abdominal abscess is one of the common causes of readmission ( 20 ), severely affecting patients’ prognosis and quality of life. According to the Extended Clavien-Dindo classification of intra-abdominal infection ( 21 ), 1 case (2.9%) reached II, 30 cases (88.2%) reached IIIa, 3 cases (8.9%) reached IIIb stage.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in Tables 1 and 2 , the length of hospital stay in IAI patients was significantly longer in terms of short-term prognosis. Studies have revealed that intra-abdominal abscess is one of the common causes of readmission ( 20 ), severely affecting patients’ prognosis and quality of life. According to the Extended Clavien-Dindo classification of intra-abdominal infection ( 21 ), 1 case (2.9%) reached II, 30 cases (88.2%) reached IIIa, 3 cases (8.9%) reached IIIb stage.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is notable that only 2 studies reported a relationship between the resection type and 30-day readmission. Asaoka et al [ 15 ] reported that laparoscopic surgery (OR 2.25; 95% CI: 1.17–4.31; P = .015) was an independent risk factor for postoperative readmission, whereas no significant difference (OR 2.039; 95% CI: 0.727–5.722; P = .168) was detected in the study performed by Zhuang et al [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…In the presented study, the readmission rate at 30 days postgastrectomy was 11.7%. The reported readmission rate was diverse among included studies; the incidence rate was 2.7%, 2.9%, and 7.2% in the 3 studies from East Asia [ 15 17 ] but was 14.2%, 14.6%, and 16.5% in the other 3 studies from the United States. [ 12 14 ] Reasons for the different readmission rates between these studies are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations